2020
DOI: 10.1002/mds.28241
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Impaired Endogenous Pain Modulation by Dopaminergic Medication in Parkinson's Disease

Abstract: Genome-wide identification of hypoxia-inducible factor binding sites and target genes by a probabilistic model integrating transcriptionprofiling data and in silico binding site prediction. Nucleic Acids Rese 2010;38(7):2332-2345. 13. Holmquist-Mengelbier L, Fredlund E, Lofstedt T, et al. Recruitment of HIF-1alpha and HIF-2alpha to common target genes is differentially regulated in neuroblastoma: HIF-2alpha promotes an aggressive phenotype. Cancer Cell 2006;10(5):413-423. 14. Uchida T, Rossignol F, Matthay MA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Dopamine receptors are expressed in a range of neurons that are distributed throughout the central nervous system, where according to the receptor classification, they may be involved in the modulation of pain perception. The neuropathological hallmark of PD (degeneration of nigrostriatal dopaminergic pathways) is believed to cause alterations in the central processing of nociceptive signals, whereas dopamine deficiency in mesocortico-limbic pathways influences affective and cognitive processes, thus modulating the interpretation of peripherally generated nociceptive signals, and contributing to the negative affective dimension of pain [1,11,12]. The involvement of dopaminergic pathways in the process of pain chronification has been reported [13].…”
Section: Dopaminementioning
confidence: 99%
“…Dopamine receptors are expressed in a range of neurons that are distributed throughout the central nervous system, where according to the receptor classification, they may be involved in the modulation of pain perception. The neuropathological hallmark of PD (degeneration of nigrostriatal dopaminergic pathways) is believed to cause alterations in the central processing of nociceptive signals, whereas dopamine deficiency in mesocortico-limbic pathways influences affective and cognitive processes, thus modulating the interpretation of peripherally generated nociceptive signals, and contributing to the negative affective dimension of pain [1,11,12]. The involvement of dopaminergic pathways in the process of pain chronification has been reported [13].…”
Section: Dopaminementioning
confidence: 99%
“…The midbrain DA reward system is a key brain structure that regulates pain and analgesia (Watanabe & Narita, 2018), and VTA is the main source of DA in this system (Sagheddu et al, 2015). In fact, DA can modulate pain at multiple levels of the nervous system(Eric H. Chudler & Dong, 1995), and numerous studies have also demonstrated that decreased DA levels may be associated with the production of pain symptoms in PD (Domenici et al, 2019;Florin, Koschmieder, Schnitzler, & Becker, 2020). Besides, Marco L.et al suggested that alterations in dopaminergic neurotransmission may be a potential factor in the marked nociceptive hyperalgesia in bromyalgia patients (Loggia et al, 2014).…”
Section: Fc Resultsmentioning
confidence: 99%
“…The types of pain that may be associated with PD are substantially varied with musculoskeletal pain occurring most frequently and central pain being the least reported but most severe [5,40,61]. There is some discussion that Parkinson's pathology has a modulating effect on pain sensation, which could amplify pain and help explain a portion of the higher incidence of chronic pain felt by Parkinson's patients, but a definitive explanation has yet to be found [63][64][65][66][67][68][69]. Pain perception is a complicated facet of human physiology and the difficulty in managing pain reflects the limited understanding [36].…”
Section: Discussionmentioning
confidence: 99%
“…The leading hypotheses as to the cause is some dysfunction in the pain pathways or processing of pain inputs within the central nervous system [62,63]. Concerning general chronic pain, some studies suggest that it is not the sensory perception that is modulated in PD, but the motivation to endure or avoid it that is altered [64]. This concept stems from studies that have shown dopamine, which is the neurotransmitter at loss in PD, to be involved in the emotional-motivation aspect of pain rather than the sensory-discriminative [65,66].…”
Section: Peripheral and Central Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation